Effect of the addition of antimicrobial agents on shore a hardness and roughness of soft lining materials - Urban, Vanessa M.; Lima, Thiago F.; Bueno, Mirian G.; Giannini, Marcelo; Arioli Filho, Joao N. [UNESP]; Almeida, Ana Lucia P. F. de; Neppelenbroek, Karin H. (Wiley-Blackwell, 2015)
Purpose: While the incorporation of antimicrobial agents into soft denture liners has been suggested as a reliable alternative treatment for denture stomatitis, it may affect the liner's properties. The effect of addition of antimicrobial agents for the treatment of denture stomatitis on the surface roughness and Shore A hardness of soft lining materials was evaluated. Materials and methods: The test groups comprised specimens (36 x 7 x 6 mm(3)) of soft materials (Softone and Trusoft) without (control) or with incorporation of drugs (nystatin, miconazole, ketoconazole, chlorhexidine diacetate, and itraconazole). Hardness (Shore A) and roughness (Ra) were evaluated after immersion of specimens (n = 10) in distilled water at 37 degrees C for 24 hours, 7 and 14 days. Data were analyzed by 3-way ANOVA/Tukey's test ( = 0.05). Results: After 14 days, an increase (p < 0.05) was observed in the hardness of soft materials with time for the modified specimens, except for itraconazole. Addition of drugs increased the Softone roughness only for the addition of miconazole and chlorhexidine (p < 0.05), and did not increase the roughness of Trusoft with time. Only chlorhexidine and itraconazole altered the roughness compared to the control for each material (p < 0.05). Conclusions: The smallest changes of hardness and roughness with time in the modified groups compared to controls were observed for itraconazole groups for both materials.
Keywords: Denture stomatitis; Denture liners; Candida albicans; Anti-infective agents; Surface properties